2019
DOI: 10.1016/j.msksp.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Agreement is very low between a clinical prediction rule and physiotherapist assessment for classifying the risk of poor recovery of individuals with acute whiplash injury

Abstract: Background: A prognostic clinical prediction rule (whiplash CPR) has been validated for use in individuals with acute whiplash associated disorders (WAD). The clinical utility of this tool is unknown.Objectives: To investigate: 1) the level of agreement between physiotherapist-and whiplash CPR-determined prognostic risk classification of people with acute WAD; 2) which clinical findings are used by physiotherapists to classify prognostic risk; and 3) whether physiotherapists plan to differ the number of treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…There are several tools available to achieve this—WhipPredict for patients with WAD, the short-form Orebro Musculoskeletal screen for WAD and non-traumatic neck pain, and StartMSK for non-traumatic neck pain (see Table 2 for availability). Research suggests that rehabilitation health care providers are not aware of prognostic indicators and do not use clinical risk screening tools for patients with neck pain [71,72]. The majority of patients will fall into the ‘low risk’ category; in other words, they should recover well with minimal treatment comprising a few sessions of advice, reassurance, and exercise.…”
Section: Promising Directions For Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…There are several tools available to achieve this—WhipPredict for patients with WAD, the short-form Orebro Musculoskeletal screen for WAD and non-traumatic neck pain, and StartMSK for non-traumatic neck pain (see Table 2 for availability). Research suggests that rehabilitation health care providers are not aware of prognostic indicators and do not use clinical risk screening tools for patients with neck pain [71,72]. The majority of patients will fall into the ‘low risk’ category; in other words, they should recover well with minimal treatment comprising a few sessions of advice, reassurance, and exercise.…”
Section: Promising Directions For Clinical Practicementioning
confidence: 99%
“…Another example would be information about likely prognosis nominated as important by patients [76], but which health care providers may not usually provide or be uncomfortable with how to deliver this information to patients. We have consistently found that physiotherapists are not well aware of the consistent predictors of poor recovery after whiplash injury [71,80], so may not routinely assess for such factors with the view of gauging prognosis. There are clinical prediction rules available to identify patients both at risk of poor recovery and those that will recover well [67,68,69] but to date the clinical uptake of these has been slow.…”
Section: Promising Directions For Clinical Practicementioning
confidence: 99%
“…The basic elements of this treatment plan are: (1) time phase after accident, which is markedly associated with disability, coping, and fear avoidance, and (2) the patient’s course of recovery since the accident, which is moderately associated with pain intensity, disability, coping, and fear avoidance. A dynamic plan of treatment, based on the modifiability of a number of prognostic psychological and physical factors by physiotherapy intervention, was developed in 2003 [ 77 ] and later adapted in 2018 [ 30 ]. Further research is needed to link the modifiable prognostic factors and underlying mechanisms to treatment goals, treatment, and patient-related outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Another survey was excluded, as it looked at which psychosocial factors physiotherapists have knowledge of, and which ones they feel are important, but again there was no discussion about ability or confidence (Overmeer et al, 2004). Three studies were excluded, as they were related to physiotherapist prognostic ability, rather than specifically the assessment of psychosocial factors (Cook et al, 2015;Dagfinrud et al, 2013;Kelly et al, 2019). A study which was found in the initial stage one scoping search, was excluded, as it was a systematic review (Gray & Howe, 2013).…”
Section: Author Contributionsmentioning
confidence: 99%